PENGUJIAN BUCKET ELEVATOR GEN.01 TM - Sukroni, Sukroni; Suwandi, Dedi; Ghozali, Muhamad; Gunawan, Leo Van (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2023)
Post-harvest agricultural products are all activities carried out from the process of handling agricultural products to the process that produces semi-finished products. Improper post-harvest handling will result in yield loss, both weight and product quality. Readiness of mature harvest and post-harvest technology will improve the quality of rice and the understanding of farmers and technology users in efforts to reduce crop losses. Bucket elevator is a tool for moving material that can be used to lift grain during the grain milling process, which can help work to move grain from the surface into the milling machine. In the Bucket Elevator test results, the effective rotational speed is 352.5 Rpm using a 1 hp 3 phase motor. The design of model 1 is the optimal bucket for lifting grain, resulting in a net weight of 243 gr/bucket contents with a maximum capacity of 280 gr/bucket. When attached to the Bucket carrier belt with 3 test results with different 1 hp motors get test results 1 = 22.5 kg/m , test 2 = 21.3 kg/m , and test 3 = 22.7 kg/m , with average result– average 22.1 kg/m. The noise test on the Bucket Elevator gets the results of noise intensity at 3 different points with an average value of point 1 (front) = 77.7 dBA, point 2 (side) = 72.0 dBA, and point 3 (top) = 77, 1dBA.